RETRACTED ARTICLE: miR-506 contributes to malignancy of cutaneous squamous cell carcinoma via targeting of P65 and LAMC1. Issue 3 (1st February 2019) - Zhou, Jian; Zhang, Ying; Han, Zhaofeng; Dong, Zhiwei; Cao, Tongtong; Wei, Aizhou; Guo, Pengfei; Meng, Qingnan
Statement of Retraction: We, the Editors and Publisher of the journal Cell Cycle, have retracted the following article: Jian Zhou, Ying Zhang, Zhaofeng Han, Zhiwei Dong, Tongtong Cao, Aizhou Wei, Pengfei Guo, and Qingnan Meng. miR-506 contributes to malignancy of cutaneous squamous cell carcinoma via targeting of P65 and LAMC1. Cell Cycle. 2019;18(3):333-345. doi:10.1080/15384101.2019.1568747. Since publication, significant concerns have been raised about the integrity of the data and reported results in the article. When approached for an explanation, the authors did not provide their original data or any necessary supporting information. As verifying the validity of published work is core to the integrity of the scholarly record, we are therefore retracting the article. The corresponding author listed in this publication has been informed. The authors agree with the retraction. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.